An evaluation of the effects of Ramadan fasting on anthropometric, metabolic and endocrine parameters - Akkoca, Muzaffer; Metin, Ziya Erokay; Topaloğlu, Oya; Tokgöz, Serhat; Cihan, Gökhan; Şan, İshak (Progress in Nutrition, 2018)
Objective: The aim of this study was to examine the effects of the energy and nutrients intake at Ramadan fasting on anthropometric measurements, metabolic and endocrine parameters. Methods: This prospective study included a total of 80 healthy volunteers, aged 19-50 years, who were fasting during the month of Ramadan. Anthropometric measurements, blood samples were taken and nutritional intake was recorded of all participants at 5 days before Ramadan(BR) and on the 27th day at the end of Ramadan (AR). The anthropometric measurements comprised height, weight, body mass index(BMI), hip-waist circumference, body fat ratio and fat mass measurements. From the blood samples, analysis was made of fasting glucose, insulin, total cholesterol, LDL-C, HDL-C and TG. From the records of food intake, energy and nutrients were calculated. The anthropometric measurements, metabolic and endocrine parameters, energy and nutrients BR and AR were compared generally. Results: In the period from BR to AR in the values, a decrease was determined in body weight (77.4±11.0, 76.2±10.7kg, p<0.01), BMI (26.1±2.6, 25.7±2.5kg/m2, p<0.001), waist circumference (94.5±9.0, 91.8±8.3cm p<0.001) and body fat ratio (24.4%±6.4%, 23.8%±5.9%, p<0.01). An increase was determined in the values of fasting glucose (83.5±7.4, 91.1±12.3mg/dl, p<0.01), insulin (8.8±4.1, 10.1±4.5µU/ml, p<0.01) and HOMA-IR (1.8±0.9, 2.2±1.1, p<0.01). There was a decrease in HDL-C levels (p<0.001). Conclusion: Ramadan fasting was observed to have positive effects on anthropometric measurements such as body weight, BMI, fat mass and waist circumference, which are cardiovascular risk factors, but no similar positive effect was seen on endocrine and metabolic parameters.